Human rights, education and sustainable development - Bonifácio, Artur Cortez; Vieira, Edson Matheus Dantas (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The right to education plays a central role in the development of contemporary societies, we cannot speak of sustainable development apart from the civilizing standards promoted by education. Thus, considering the importance of the theme, this work will focus on the effectiveness of this right in the Brazilian legal system, which will be done through a case study related to the judgment issued in the records of Extraordinary Appeal 1.008.166/SC. Specifically, it will seek to address the issue within the logic of human rights, the 2030 Agenda and the legal provisions established in the Brazilian legal order. The methodology used, therefore, will be the case study, with contributions in the bibliographical research. The relevance of the theme lies in the need to promote the realization of the fundamental right to education, especially basic education. The results obtained with the research revealed the importance and essentiality of this right, which does not have a merely programmatic content and affirms itself as a norm of full effectiveness and direct and immediate applicability. Finally, this work contributes to the understanding of the fundamental right to education from the theoretical and practical point of view.
Keywords: Human rights; Development; Education